Using a choose-your-own-adventure game to explore the complexity of workplace compassion. Issue 2 (3rd April 2022) - Leach, Rebecca B.; Kim, Heewon
Abstract : Course : Organizational Communication, Business/Professional Communication . Objectives : This activity is designed to help students respond to their peers' challenges in a more compassionate and helpful way. At the end of the activity, students will be able to identify appropriate displays of compassion at work.